Effect of embedded the post-training recovery services following resistance training on muscular strength in vietnamese national para powerlifting athletes - a case study - Thi My, H. L.; Viet, B. V.; Minh, T. T.; Hooi, L. B.; Siswantoyo (International Journal of Disabilities Sports and Health Sciences, 2024)
Purpose: The aim of this study was to assess and compare the muscular strength with bench press test and dominant hand-grip test between pre-intervention and post-intervention.